Registration of H2O and SiO masers in the Calabash Nebula to confirm the planetary nebula paradigm. Issue 1 (31st January 2018) - Dodson, R; Rioja, M; Bujarrabal, V; Kim, J; Cho, S H; Choi, Y K; Youngjoo, Y
Abstract: We report on the astrometric registration of very long baseline interferometry images of the SiO and H2 O masers in OH 231.8+4.2, the iconic proto-planetary nebula also known as the Calabash nebula, using the Korean VLBI Network and source frequency phase referencing. This, for the first time, robustly confirms the alignment of the SiO masers, close to the asymptotic giant branch star, driving the bilobe structure with the water masers in the outflow. We are able to trace the bulk motions for the H2 O masers over the last few decades to be 19 km s −1 and deduce that the age of this expansion stage is 38 ± 2 yr. The combination of this result with the distance allows a full 3D reconstruction and confirms that the H2 O masers lie on and expand along the known large-scale symmetry axis and that the outflow is only a few decades old, so mass loss is almost certainly ongoing. Therefore, we conclude that the SiO emission marks the stellar core of the nebular, the H2 O emission traces the expansion, and there must be multiple epochs of ejection to drive the macro-scale structure.